ESTRUCTURA MUSCULAR FEMORAL DE XEROMELISSINAE (HYMENOPTERA, COLLETIDAE) (Acta Entomológica Chilena, 2022)
Chüicola (Chüicola) rubriventris; Ch. (Oediscelis) vemalis; Ch. (Stenoediscelis) inermis; Ch. (Idioprosopis) chalcidiformis;Chilimelissa luisa; Xenochilicola mamigna y Xeromelissa wümattae. In all the species with enlargedfemora, the flexor muscle is highly enlarged and inserted dorsally in the basitibial area; the extensormuscle is not modified. The enlargement of the tibia is not related to the tarsal muscle size. The tibialmuscles of the females and the males with not enlarged posterior femora are unmodified. Neofideliaprófuga (Fideliidae) and Leucospis hopei (Leucospidae) are similar, when compared with Xeromelissinae,but the shape of the tibia and other characters point out a different function. The enlarged femora ofPararhophites orobinis (Anthophoridae), shows a larger extensor muscle. The presence of graspingstructures in the posterior región of the males of Xeromelissinae suggest a role in mating.